Mitochondrial PGAM5−Drp1 signaling regulates the metabolic reprogramming of macrophages and regulates the induction of inflammatory responses - Bang, Bo-Ram; Miki, Haruka; Kang, Young Jun (Frontiers in Immunology, 2023)
Macrophages play a critical role in the regulation of inflammation and tissue homeostasis. In addition to their vital functions for cell survival and physiology, mitochondria play a crucial role in innate immunity as a platform for the induction of inflammatory responses by regulating cell signaling and dynamics. Dynamin-related protein 1 (Drp1) plays a role in the induction of inflammatory responses and the subsequent development of various diseases. PGAM5 (phosphoglycerate mutase member 5) is a mitochondrial outer membrane phosphatase that dephosphorylates its substrate, Drp1. Previous studies showed that PGAM5 regulates the phosphorylation of Drp1 for the activation of NKT cells and T cells. However, it is not clear how PGAM5 regulates Drp1 activity for the induction of inflammation in macrophages. Here, we demonstrate that PGAM5 activity regulates the dephosphorylation of Drp1 in macrophages, leading to the induction of proinflammatory responses in macrophages. In TLR signaling, PGAM5 regulates the expression and production of inflammatory cytokines by regulating the activation of downstream signaling pathways, including the NF-B and MAPK pathways. Upon LPS stimulation, PGAM5 interacts with Drp1 to form a complex, leading to the production of mtROS. Furthermore, PGAM5-Drp1 signaling promotes the polarization of macrophages toward a proinflammatory phenotype. Our study further demonstrates that PGAM5-Drp1 signaling promotes metabolic reprogramming by upregulating glycolysis and mitochondrial metabolism in macrophages. Altogether, PGAM5 signaling is a linker between alterations in Drp1-mediated mitochondrial dynamics and inflammatory responses in macrophages and may be a target for the treatment of inflammatory diseases.